2020
DOI: 10.1093/rheumatology/keaa595
|View full text |Cite
|
Sign up to set email alerts
|

Changing evidence over time: updated meta-analysis regarding anti-TNF efficacy in childhood chronic uveitis

Abstract: Objective To summarize evidence regarding efficacy of anti-TNFα in childhood chronic uveitis, refractory to common DMARDs. Methods An updated systematic search was conducted between November 2012 and January 2020. Studies investigating the efficacy of anti-TNFα therapy, in children of ages <16 years, as the first biologic treatment for childhood chronic uveitis, refractory to topical and/or systemic steroid and at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Another reason may be that we have incorporated NIU children into this study. Children with NIU have a lower prevalence of severe complications[28], and have a higher respondence rate which was substantiated by two reviews [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Another reason may be that we have incorporated NIU children into this study. Children with NIU have a lower prevalence of severe complications[28], and have a higher respondence rate which was substantiated by two reviews [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…There is also data suggesting that the more severe asthma, the higher the risk of ADHD and this may also influence the emergence of behavioural changes seen after initiation of ICS in children with a higher genetic susceptibility for one or both disorders [ 12 , 32 ]. Anxiety disorder and depression may also be more common in children with asthma, especially in those with uncontrolled asthma symptoms [ 33 ]. In short, not all behavioural changes after initiation of ICS may be true ADEs.…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic reviews identified that adalimumab is better at controlling intra-ocular inflammation in JIA-associated uveitis than infliximab ( 217 , 232 ). The data from the BiKeR JIA registry showed that there was a tendency for more occurrence of JIA-associated uveitis in the Etanercept group than in the biologic naïve group although the difference was not significant (1.9/100 PY vs. 1.4/100 PY, p = 0.09) ( 233 ).…”
Section: Non-infectious Uveitismentioning
confidence: 99%